(untitled) (Damascus University Journal of agriculture sciences, 2026)
The susceptibility of some grapevine Vitis vinifera cultivars (Al-Salti, Al-aswad, Al-ziyni, Al-baladi, Al-hulwani) grown in Sweida Governorate to infection with dead arm disease caused by the fungus Phomopsis viticola, was tested during the 2020 season, Within the vineyards (natural infection), and in the greenhouse (Industrial infection) at the Scientific Agricultural Research Center in Sweida. Field and semi-field results showed that the “Al-Salti” cultivar was the most susceptible to the disease tested, with an industrial infection rate of 100%, followed by the “Al-aswad” and “Al-ziyni” cultivars, with moderate or moderate susceptibility (80 and 75%), respectively. While both the “Al-baladi” and “Al-Hulwani” cultivars recorded a lower susceptibility to dead arm disease (35 and 25%), respectively. Analysis of the Contrasts in the average degree of injury severity in each cultivar showed that there were statistically significant differences in injury severity at the level of 0.05, and these differences are due to the cultivar. The value of the theta correlation coefficient () showed the strength of the correlation between the cultivar and injury severity, as it reached 81% at a significant level. 0.05. The test for estimating the proportion of carbohydrates in the canes showed an inverse relationship with the susceptibility to infection. The ANOVA test showed that there was a significant effect of the cultivar on the concentration of carbohydrates. The average concentration of carbohydrates in the “Al-Salti” cultivar was the lowest at 51.72%, with significant differences with the rest of the cultivars at the level of The significance is 0.05, and the highest is in the “Al-Baladi” and “Al-Hulwani” cultivars, which are less susceptible to infection, 56.08% and 56.46%, respectively. This confirms the role of carbohydrates in the defense mechanism against the pathogen.